Ecosystem models for a central bank digital currency: Analysis framework and potential models - Youming Liu; Francisco Rivadeneyra; Edona Reshidi; Oleksandr Shcherbakov; André Stenzel (Bank of Canada, 2024)
For an intermediated central bank digital currency (CBDC) to be successful, central banks will need to develop sustainable economic models where intermediaries and end users derive value and central banks achieve their policy goals. This note presents a framework for analyzing different economic models of CBDC ecosystems. We analyze the trade-offs of three main CBDC ecosystem models, each with different levels of central bank involvement in activities of the ecosystem and the usage of different policy levers. The policy levers considered in the framework are control over intermediary access to the CBDC network, prices and quality standards. Our analysis suggests that a central bank provision of network infrastructure enables direct control over intermediary access requirements, prices and quality standards upstream. Providing a central bank digital wallet increases development costs but allows the central bank to set quality standards downstream and to promote competition. Delegating the network service to a regulated entity reduces costs for the central bank but may limit its strategic autonomy to control upstream pricing and intermediary access. Our analysis also suggests several areas of future research: central bank pricing models, intermediary revenue models, and quality and privacy standards.
Keywords: E; E5; E58; E6; E61; L; L5; 330; Central bank research; Digital currencies and fintech; Financial services